2001
DOI: 10.1051/animres:2001102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplying leucine and methionine to early-lactating cows fed silage-concentrate based diets with a calculated deficiency in leucine and methionine

Abstract: -In a 2 × 2 factorial approach the productive and metabolic response of 24 multiparous Brown Swiss cows fed rations calculated to be deficient in leucine (0.9-fold of requirements) and methionine (0.8-fold) to supplementation either of one or both of these amino acids were investigated. On a dry matter basis the rations consisted of 29% grass silage, 20% maize silage, 6% hay, and 45% concentrate. Blood plasma amino acid data confirmed the intended difference in metabolic supply of leucine and methionine keepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
(27 reference statements)
5
17
1
Order By: Relevance
“…Our findings are in agreement with minor effects of additional Leu on milk yield and composition reported in other studies (e.g. Kröber et al, 2001;Huhtanen et al, 2002;Korhonen et al, 2002;Křížová et al, 2008). On the other hand, in a dose response study (duodenal infusions of 0, 40, 80 and 120 g/day Leu) Rulquin and Pisulewski (2006) found that milk yield was not affected by the treatments, whereas the content and yield of protein and casein varied quadratically (P < 0.05), with a maximum reached by 40 g/day Leu.…”
Section: Intake Of Nutrients and Milk Yield And Compositionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings are in agreement with minor effects of additional Leu on milk yield and composition reported in other studies (e.g. Kröber et al, 2001;Huhtanen et al, 2002;Korhonen et al, 2002;Křížová et al, 2008). On the other hand, in a dose response study (duodenal infusions of 0, 40, 80 and 120 g/day Leu) Rulquin and Pisulewski (2006) found that milk yield was not affected by the treatments, whereas the content and yield of protein and casein varied quadratically (P < 0.05), with a maximum reached by 40 g/day Leu.…”
Section: Intake Of Nutrients and Milk Yield And Compositionsupporting
confidence: 94%
“…Similarly, Kröber et al (2001) confirmed that the variation in supply was clearly reflected in different plasma levels of the respective AA after feeding the experimental diets for 18 days on average. The response in terms of blood plasma concentrations of other AA to Leu supplementation is scarce and inconsistent.…”
Section: Blood Parameters and Plasma Aasupporting
confidence: 70%
See 2 more Smart Citations
“…Korhonen et al (2000) mentioned His as the first limiting AA in diets based on grass silage and, according to Vanhatalo et al (1999) His has been identified as a potentially limiting AA for milk production. Other authors mentioned as limiting the combinations of Met with Leu (Krober et al, 2001) and/or with His and Arg (Xu et al, 1998). The problem of limiting AA has been relatively well investigated in studies on the supply of Met and Lys but not enough data are available for other AA or their combinations.…”
Section: Introductionmentioning
confidence: 99%